BENTUK PENYIMPANGAN PRINSIP KESANTUNAN BERBAHASA DALAM DISKUSI - Nirmalasari Makmur; H. Rustam Efendy Rasyid; H. Aminuddin Mamma (Cakrawala Indonesia, 2019)
This study aims to describe the deviations and compliance with the principle of politeness in language that occurs in discussion in class VII students of SMP Negeri 1 Pancarijang. The method used in this research is descriptive qualitative method. The technique used in collecting data uses listening techniques, record techniques and note taking techniques. Data analysis uses the pragmatic equivalent method. Data deviations from the politeness principle of language consists of six maxims, including maxims of wisdom, sympathy, appreciation, generosity, simplicity and consensus. Among the maxim of politeness, the maxim that is most distorted in terms of word choice and polite manner of discussion is the maxim of appreciation. Meanwhile, the maxim that is the most followed in terms of word choice and polite discussion is the maxim of wisdom.